Glycoengineering of NK Cells with Glycan Ligands of CD22 and Selectins for B‐Cell Lymphoma Therapy. Issue 7 (14th December 2020) - Hong, Senlian; Yu, Chenhua; Wang, Peng; Shi, Yujie; Cao, Weiqian; Cheng, Bo; Chapla, Digantkumar G.; Ma, Yuanhui; Li, Jie; Rodrigues, Emily; Narimatsu, Yoshiki; Yates, John R.; et al.
Abstract: CD22, a member of Siglec family of sialic acid binding proteins, has restricted expression on B cells. Antibody‐based agents targeting CD22 or CD20 on B lymphoma and leukemia cells exhibit clinical efficacy for treating these malignancies, but also attack normal B cells leading to immune deficiency. Here, we report a chemoenzymatic glycocalyx editing strategy to introduce high‐affinity and specific CD22 ligands onto NK‐92MI and cytokine‐induced natural killer cells to achieve tumor‐specific CD22 targeting. These CD22‐ligand modified cells exhibited significantly enhanced tumor cell binding and killing in vitro without harming healthy B cells. For effective lymphoma cell killing in vivo, we further functionalized CD22 ligand‐modified NK‐92MI cells with the E‐selectin ligand sialyl Lewis X to promote trafficking to bone marrow. The dual‐functionalized cells resulted in the efficient suppression of B lymphoma in a xenograft model. Our results suggest that natural killer cells modified with glycan ligands to CD22 and selectins promote both targeted killing of B lymphoma cells and improved trafficking to sites where the cancer cells reside, respectively. Abstract : We report the use of a chemoenzymatic glycocalyx editing strategy to create CD22‐specific ligands and sialyl Lewis X on NK cells (NK‐92MI or CIK cells) to target and eradicate B‐lymphoma efficiently.